Difficulties of nursing professionals in care management for cancer patients in palliative care (Research, Society and Development, 2020)
Palliative Care is provided to patients with progressive and irreversible diseases when there is no therapeutic possibility of cure. This care is not intended to delay or accelerate death, but only to improve the quality of life in the terminally ill. Knowing how to carry out an effective care management for patients at this stage of life is of paramount importance to offer greater comfort, since healing at this time is not a priority and could even lead to greater suffering for the patient and their families. In view of this, the objective of the study was to understand the difficulties of nursing professionals in the management of care for cancer patients in palliative care. It is a qualitative study, of the integrative review type, with three articles selected in the Virtual Health Library (VHL) and Pubmed databases between the period of 2015 and 2020. After reading, analyzing and interpreting the data, we can to verify that the main difficulty listed in the management of care was the lack of professional training, since the complexity of cancer care for palliative patients requires both technical-scientific and interpersonal skills. There is a need for new research to better elucidate the difficulties of nursing professionals in managing the area of ​​palliative care to promote better comfort and excellent care in this very delicate stage of life.